2013
DOI: 10.1177/0042098013497407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Housing Vouchers on Crime in US Cities and Suburbs

Abstract: This paper tests the common belief that subsidised housing contributes to higher crime rates. To do this, panel data on over 200 US cities are used and fixed effects models are estimated to control for unobserved differences between cities that may affect both voucher use and crime. Additionally, models are estimated that focus on the suburbs, to see if the steady increase in vouchers there has had any effect on crime. In cities, it is found that vouchers have a weak, negative relationship with violent crime r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The research on this issue is substantial, but results are mixed. If there is a consensus on the Housing Choice Voucher Program/Section 8, it is that there is a weak association between housing vouchers and crime (Lens, 2014). 3 The preponderance of studies of low-income housing developments and crime show some association between low-income housing developments and crime, but LIHTC housing may be different.…”
Section: Crimementioning
confidence: 99%
“…The research on this issue is substantial, but results are mixed. If there is a consensus on the Housing Choice Voucher Program/Section 8, it is that there is a weak association between housing vouchers and crime (Lens, 2014). 3 The preponderance of studies of low-income housing developments and crime show some association between low-income housing developments and crime, but LIHTC housing may be different.…”
Section: Crimementioning
confidence: 99%
“…Across all regression models, a change in public housing was positively correlated with a change in crime in affected census tracts, suggesting that public housing is associated with crime but low-income housing is not. Lens (2013) examined changes in crime rates between 1997 and 2008 in 215 large US cities and changes in rates of subsidized housing. 22 He found little association, suggesting that changes in the public and subsidized housing stock had little impact on city-level crime rates.…”
Section: B Low-income Housingmentioning
confidence: 99%
“…However, though there is some reasonable evidence that well-maintained vegetation may signal or cause lower crime, there is little quality evidence that public housing design itself is a strong predictor of crime. Public housing design may be less consequential for crime than for concentrating poor people in neighborhoods (Lens 2013). …”
Section: F Summarymentioning
confidence: 99%
“…Additionally, poverty rates have been found to decline in high-poverty neighborhoods after the completion of LIHTC developments, and in general, there is little evidence that the LIHTC program contributes to poverty concentration or residential segregation (Ellen, Horn, & O’Regan, 2016; Freedman & McGavock, 2015; Horn & O’Regan, 2011). There are mixed findings regarding the impact of affordable housing on the stability of the surrounding community, but generally, associations between subsidized housing developments and neighborhood crime are weak or insignificant, suggesting that some concerns about affordable housing may be misguided (Albright et al, 2013; Ellen, Lens, & O’Regan, 2012; Freedman & Owens, 2011; Lens, 2014). In fact, one study demonstrated that LIHTC developments built in the poorest neighborhoods resulted in significant reductions in violent crime, but not property crime (Freedman & Owens, 2011).…”
Section: Introductionmentioning
confidence: 99%